Homogeneous Pt nanostructures surface functionalized with phenylboronic acid phosphonic acid derivatives as potential biochemical nanosensors and drugs: SERS and TERS studies. Issue 6 (30th January 2023) - Proniewicz, Edyta; Gralec, Barbara; Ozaki, Yukihiro
Abstract: Here, surface‐enhanced Raman scattering (SERS) and tip‐enhanced Raman scattering (TERS) were used to characterize the selective adsorption of N ‐substituted 4‐[( N H‐R)(phosphono)‐ S ‐methyl]phenylboronic acids on the surface of platinum nanoparticles (PtNPs) from an aqueous solution and from air. The nature of the interaction of the studied compounds with the PtNPs/H2 O and PtNPs/air interfaces was discussed and compared. For this purpose, 4‐[( N ‐anilino)(phosphono)‐ S ‐methyl]phenylboronic acid (1‐PBA‐PA) and its two analogs (2‐PBA‐PA and bis{1‐PBA‐PA}) as well as the PtNPs were synthesized in surfactant/ion‐free solution via a synthetic route that allows control of the size and morphology of the NPs. The positively charged PtNPs with a size of ~12 nm were characterized by ultraviolet–visible spectroscopy (UV–Vis), dynamic light scattering (DLS), scanning electron microscopy (SEM), and X‐ray powder diffraction (XRD). Abstract :